The cost-effectiveness of policies for the safe and appropriate use of injection in healthcare settings - Dziekan Gerald; Chisholm Daniel; Johns Benjamin; Rovira Juan; Hutin Yvan J.F (The World Health Organization, 2003)
OBJECTIVE: Poor injection practices transmit potentially life-threatening pathogens. We modelled the cost-effectiveness of policies for the safe and appropriate use of injections in ten epidemiological subregions of the world in terms of cost per disability-adjusted life year (DALY) averted. METHODS: The incidence of injection-associated hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) infections was modelled for a year 2000 cohort over a 30-year time horizon. The consequences of a "do nothing" scenario were compared with a set of hypothetical scenarios that incorporated the health gains of effective interventions. Resources needed to implement effective interventions were costed for each subregion and expressed in international dollars (I$). FINDINGS: Worldwide, the reuse of injection equipment in the year 2000 accounted for 32%, 40%, and 5% of new HBV, HCV and HIV infections, respectively, leading to a burden of 9.18 million DALYs between 2000 and 2030. Interventions implemented in the year 2000 for the safe (provision of single-use syringes, assumed effectiveness 95%) and appropriate (patients-providers interactional group discussions, assumed effectiveness 30%) use of injections could reduce the burden of injection-associated infections by as much as 96.5% (8.86 million DALYs) for an average yearly cost of I$ 905 million (average cost per DALY averted, 102; range by region, 14-2293). Attributable fractions and the number of syringes and needles required represented the key sources of uncertainty. CONCLUSION: In all subregions studied, each DALY averted through policies for the safe and appropriate use of injections costs considerably less than one year of average per capita income, which makes such policies a sound investment for health care.